2021
DOI: 10.1111/gcb.15760
|View full text |Cite
|
Sign up to set email alerts
|

Thermal optima of gross primary productivity are closely aligned with mean air temperatures across Australian wooded ecosystems

Abstract: Gross primary productivity (GPP) of wooded ecosystems (forests and savannas) is central to the global carbon cycle, comprising 67%–75% of total global terrestrial GPP. Climate change may alter this flux by increasing the frequency of temperatures beyond the thermal optimum of GPP (Topt). We examined the relationship between GPP and air temperature (Ta) in 17 wooded ecosystems dominated by a single plant functional type (broadleaf evergreen trees) occurring over a broad climatic gradient encompassing five ecore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 91 publications
1
28
0
Order By: Relevance
“…We acknowledge that relationships of stem growth with temperature are not necessarily causative, particularly because temperature effects were likely confounded with soil moisture content (i.e., indicated by a strong negative correlation). Nonetheless, bell-shaped relationships between monthly stem growth and temperature were consistent with similar shaped relationships between gross primary productivity and mean air temperature that controlled for other climate variables across a broad range of Australian wooded ecosystems [91]. The importance of temperature was not evident in seasonal LMEMs, when competition and rainfall were of greater importance.…”
Section: Species Climate and Competition Interact To Drive The Stem Growth Of Temperate Eucalyptssupporting
confidence: 68%
“…We acknowledge that relationships of stem growth with temperature are not necessarily causative, particularly because temperature effects were likely confounded with soil moisture content (i.e., indicated by a strong negative correlation). Nonetheless, bell-shaped relationships between monthly stem growth and temperature were consistent with similar shaped relationships between gross primary productivity and mean air temperature that controlled for other climate variables across a broad range of Australian wooded ecosystems [91]. The importance of temperature was not evident in seasonal LMEMs, when competition and rainfall were of greater importance.…”
Section: Species Climate and Competition Interact To Drive The Stem Growth Of Temperate Eucalyptssupporting
confidence: 68%
“…Moreover, rice crop has a higher benefit from e[CO 2 ] than wheat. The optimal temperature for gross primary productivity (GPP) was found to be associated with growth temperature; the higher the growth temperature, the higher the optimal temperature (Bennett et al, 2021;Huang et al, 2019) Previous studies showed an exponential response of Tr and VPD to leaf temperature (Greer, 2019) or air temperature (Grossiord et al, 2020). A positive response was also determined under optimal leaf temperatures in this study (Figure 2C,D), suggesting the response of Tr and VPD to leaf or air temperature and to optimal leaf temperature in a similar manner.…”
Section: Discussionmentioning
confidence: 99%
“…The shift in T opt reflects a considerable capacity to adjust their photosynthetic characteristics to their growth environment (Yamori et al, 2013). A higher T opt is associated with ecosystems from warmer climates (Bennett et al, 2021; Huang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…High temperatures and associated deficits in atmospheric vapour pressure provide challenges for the ability of plants to regulate water loss and to maintain photosynthesis. A synthesis across 17 OzFlux wooded ecosystems demonstrates strong alignment between the thermal optima of GPP and mean daytime air temperatures, indicating ecosystem scale photosynthesis has adjusted to past thermal regimes (Bennett et al, 2021). Although it currently seems that GPP in Australian broadleaf evergreen forests is buffered against small increases in air temperature, the shape of this relationship and the response of ER to rising temperatures will determine the sustainability of Australian carbon sinks into the future (Bennett et al, 2021; Duffy et al, 2021; Griebel, Bennett, et al, 2020; van Gorsel et al, 2016).…”
Section: Lesson 1—ozflux Ecosystems Extend Our Understanding Of the C...mentioning
confidence: 99%